Some Remarks on Strouthophagoi Tribes - Miziur-Moździoch, Maja (Polskie Towarzystwo Filologiczne, 2018)
This paper is part of the project “Ptolemy’s Zoo: Animals in Hellenistic Egypt” which has been realised within the “Sonata” programme 2015/19/D/HS3/03032 financed by the Polish National Science Centre (NCN) and conducted in the Polish Classical Association (Societas Philologa Polonorum, PTF)
Keywords: Ptolemy’s Zoo; animals in Hellenistic Egypt